Practices in concurrent engineering - Ellis, L.W.; Curtis, C.C. (Proceedings 1992 IEEE International Engineering Management Conference: Managing in a Global Environment, IEMC 1992, 1992)
To describe concurrent engineering, one must remember the old story of blind individuals attempting to characterize an elephant by feeling different body parts. The issue seems not to be just R&D cycle times, but the entire innovation cycle time process from conception of an idea ~ often in marketing not R&D -, to its final delivery to a customer - often through down-stream firms not under the R&D company's control. From the recency of many sources in the literature, this shift to a time orientation is itself rather recent. Two threads seem to have emerged: First, there is a need to address cycle-time reduction on existing products and services, both in manufacturing and administration, as an implementation management issue relating to the order-to-delivery cycle, in which engineering may be a limited associate. Also, necessary is the innovation management issue of reducing the cycle time from marketing concept to proquct introduction into the implementation process, which is the main thrust of concurrent engineering. In late 1991, a survey was conducted, first, to seek to establish a better working definition of cycle time within the two overall areas of current operations and new product development, and second, to determine the relationships between cycle time so defined and company size or profitability. The survey questionnaire was mailed to 99 medium-to-large high technology manufacturing companies in Connecticut, and yielded 48 responses, with 35 of them usable. The results confirmed the impression given by the literature that the concept was better established in current operations than in innovation management. While some do use the concept of cycle time in their new product development sub-cycles, most do not track time spent on either end of the cycle, from idea to design on the near end, or at the far end through shipment and subsequent service to the customer. Measures of size did not correlate with any of the development measures, while they did with some of the operations measures. Thus, while in concept, concurrent engineering appears to be a goal of multi-functional co-operation, a survey of the manner in which a limited number of firms actually operate seems still focused on functional specializations. © 1992 IEEE.
1 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc. IEEE Int. Eng. Manag. Conf.: Manag. Global Environ., IEMC
Keywords: Commerce; Concurrent engineering; Cycle time reduction; Environmental management; Implementation managements; Implementation process; Innovation management; Manufacturing companies; Marketing; Marketing concept; New product development; Product design; Product development; Products and services; Surveys; dept.acc